Identity Imperialism and Nation Building: Governance, Corruption, and Separatism in Nigeria - Oguejiofor, Princewilliams Odera; Akogwu, Chukwunonso Joseph; Okonkwo, Arinze Emmanuel (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2025)
This paper studies how Nigeria’s national unity, governance, and socioeconomic growth have been structurally weakened by the externally imposed identity that was a legacy of British colonialism. It also examines how this has fuelled ethnic polarisation, corruption, and separatist movements. Based on the Centre-Periphery and Psycho-Cultural Conflict theories, the study uses qualitative content analysis of secondary data to explain how imposed colonial identity impedes genuine nation-building and good governance. By methodically connecting identity imperialism to deficiencies in governance and development issues, this study closes a significant gap. The way that legal frameworks sustain identity fragmentation is further demonstrated by an analysis of the 1999 constitutional of Nigeria. The study concluded with evidence-based recommendations that highlight constitutional changes that promote fiscal federalism and inclusive national discourse as necessary conditions for long-term national development and cohesion.